The Role of Customer Experience in Mediating Experiential Marketing on Customer Loyalty at Flaurent Salon Yogyakarta - Setiawan, Marcella Devina; Ed Radianto , Wirawan (Journal Research of Social Science, Economics, and Management, 2025)
The beauty salon industry in Indonesia has experienced significant growth, particularly in the service sector, which dominates 43.69% of the creative industry market. This study investigates the relationship between experiential marketing, customer experience, and customer loyalty at Flaurent Salon in Yogyakarta. The research approach used is quantitative; data were collected through questionnaires distributed to 83 consumers who are members of the salon. The findings reveal that experiential marketing significantly influences customer experience (? = 0.669, p < 0.05) and, in turn, customer loyalty (? = 0.196, p < 0.05). Additionally, experiential marketing directly affects customer loyalty (? = 0.574, p < 0.05). These results underscore the necessity for service-based companies to enhance their marketing strategies to foster loyalty through improved customer experiences. This study successfully demonstrates significant relationships between experiential marketing, customer experience, and customer loyalty in the context of Flaurent Salon, Yogyakarta. It provides insights for Flaurent Salon to refine its marketing efforts and ensure long-term customer retention.